The story of Jazz - Stearns, Marshall Winslow (Oxford University Press, 1956)
The effect of jazz upon American culture and the American character has been all-pervasive. This superlative history is the first and the most renowned systematic outline of the evolution of this unique American musical phenomenon. Stearns begins with the joining of the African Negro's musical heritage with European forms and the birth of jazz in New Orleans then follows its course through the era of swing and bop to the beginnings of rock in the 50s, vividly depicting the great innovators, and covering such technical elements as the music's form and structure.